A STUDY OF SPEAKING ANXIETY LEVEL BETWEEN FIRST-YEAR AND SECOND-YEAR ENGLISH EDUCATION DEPARTMENT STUDENTS AT THE UNIVERSITY OF ISLAM MALANG - Ahmad Fauzi (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Anxiety in speech or oral communication is emotions or nervousness, dread, and worry encountered by people before, during, or after public speaking. The study aims to describe the anxiety level of first-year and second-year English Education Department Students at the University of Islam Malang. The study was built in a quantitative descriptive method. The populations of this study were 30 students which were sampled by doing random sampling from first-year and second-year students. The data were collected using PSCAS (Public Speaking Class Anxiety Scale). The study's findings showed that the students’ anxiety score indicated the medium level of speaking anxiety by the number of mean 55.60 – 56.47. It indicates that the first-year students took a higher score of speaking anxiety than the second-year students. The differences resulted that the t value resulted in 0.292, and it is over 0.01 which is the difference of speaking anxiety score between first-year and second-year students are not significantly different, and the significant value for this study is 0.590 which is the significant value is also under the 0.01 level. Based on the finding of the study, it is delivered to the English teachers that the number of anxiety in the student got the medium-level, both first-year and second-year so that the teachers are supposed to make the good and nice treatment for the students like giving some “sedative word” that makes the students feel like there’s nothing to lose even if they did a mistake, etc.